Pístis—‮fsṭs‬‎: A Greek and Roman Bill of Trust in Palestine - Monnickendam, Yifat (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2025)
The term pistis, in its legal context, refers to various forms of trusts, loans, securities, credits, guarantees, and means of inheritance. One of its uses in Greek Egyptian papyri was interpreted as referring to title-transfer security or to fictitious ownership. This paper adds rabbinic sources from Greco-Roman Palestine to the discussion on pistis. The comparison sheds light on the rabbinic sources, as well as expands our understanding of the use and spread of a Greek legal term and concept in the eastern Roman Empire. It therefore serves as a test case for the importance of rabbinic literature as a source in the study of Greek and Roman legal traditions, supplying new evidence for using this term as referring to fictitious ownership and for its use as referring to title-transfer security. This use of the term pistis changes in the Babylonian Talmud, preserving only echoes of its original meaning.